A Chromosome-level Genome Assembly of the Highly Heterozygous Sea Urchin Echinometra sp. EZ Reveals Adaptation in the Regulatory Regions of Stress Response Genes. (26th September 2022) - Ketchum, Remi N; Davidson, Phillip L; Smith, Edward G; Wray, Gregory A; Burt, John A; Ryan, Joseph F; Reitzel, Adam M
Abstract: Echinometra is the most widespread genus of sea urchin and has been the focus of a wide range of studies in ecology, speciation, and reproduction. However, available genetic data for this genus are generally limited to a few select loci. Here, we present a chromosome-level genome assembly based on 10x Genomics, PacBio, and Hi-C sequencing for Echinometra sp. EZ from the Persian/Arabian Gulf. The genome is assembled into 210 scaffolds totaling 817.8 Mb with an N50 of 39.5 Mb. From this assembly, we determined that the E. sp. EZ genome consists of 2 n  = 42 chromosomes. BUSCO analysis showed that 95.3% of BUSCO genes were complete. Ab initio and transcript-informed gene modeling and annotation identified 29, 405 genes, including a conserved Hox cluster. E. sp. EZ can be found in high-temperature and high-salinity environments, and we therefore compared E. sp. EZ gene families and transcription factors associated with environmental stress response ("defensome") with other echinoid species with similar high-quality genomic resources. While the number of defensome genes was broadly similar for all species, we identified strong signatures of positive selection in E. sp. EZ noncoding elements near genes involved in environmental response pathways as well as losses of transcription factors important for environmental response. These data provide key insights into the biology of E. sp. EZ as well as the diversification of Echinometra more widely and will serve as a useful tool for the community to explore questions in this taxonomic group and beyond.